OPTIMASI KONSENTRASI SUBSTRAT KULIT SINGKONG (Manihot esculenta CRANTZ.) DAN LAMA FERMENTASI TERHADAP AKTIVITAS FILTER PAPERASE DARI KAPANG Trichoderma viride FNCC 6013 - Ananda Dama Sastri, I Gst. Ayu; Anggreni, A.A.Made Dewi; Ganda Putra, G.Putu (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2015)
The aims of this study was to determine the optimum substrate concentration of cassava peel and fermentation time on crude cellulase activity from Trichoderma viride FNCC 6013. Optimization on crude cellulase activity from Trichoderma viride were calculated using the response surface method. Central Composite Design was used to study the effect of optimum substrate concentration of cassava peel and fermentation time on maximum crude cellulase activity (filter paperase). The results showed that 3.14% substrate concentration of cassava peel and 7.26 days fermentation produces maximum crude cellulase activity (filter paperase), amounting to 0.099 Units/mL.
Keywords: 29